Deans in Canadian Higher Education - Konrad, Abram G. (Canadian Journal of Higher Education, 1980)
This article presents a profile of deans in Canadian higher education - their background, career patterns, role characteristics, and professional development needs. Data were collected by a questionnaire mailed to all deans and directors in public degree-granting institutions in Canada. Deans were found to be much like their professional colleagues, and they differed little by major faculty and geographical region. Their identification of areas of strength and needs formed the basis for deriving some implications for profes- sional development in the deanship.